Evaluation of Regional‐Scale Soil Moisture‐Surface Flux Dynamics in Earth System Models Based on Satellite Observations of Land Surface Temperature. Issue 10 (29th May 2019) - Gallego‐Elvira, Belen; Taylor, Christopher M.; Harris, Phil P.; Ghent, Darren
Abstract: There is a lack of high‐quality global observations to evaluate soil drying impacts on surface fluxes in Earth system models (ESMs). Here we use a novel diagnostic based on the observed warming of the land relative to the atmosphere during dry spells (relative warming rate, RWR) to assess ESMs. The ESMs show that RWR is well correlated with changes in the partition of surface energy between sensible and latent heat across dry spells. Therefore, comparisons between observed and simulated RWR reveal where models are unable to capture a realistic soil moisture‐heat flux relationship. The results show that in general, models simulate dry spell ET dynamics well in arid zones while decreases in evaporative fraction appear excessive in some models in continental climate zones. Our approach can help guide land model development in aspects that are key in simulating extreme events like heat waves. Plain Language Summary: We present a methodology to assess how land evapotranspiration (ET) responds to soil moisture (SM) in climate models across the world. Our method is based on looking at the observed versus modeled evolution of land surface temperature and the overlying air temperature during rain free periods, when SM decreases and limits the amount of land ET. We observed a good relationship between modeled ET and the modeled relative evolution of these temperatures during dry periods. Therefore, our method can be used to evaluate how realistic are modeled SM‐ET relationships when soils are drying. Our results show that in general, models capture fairly well the influence of SM on ET in arid climate zones, while they perform less well in continental climate zones. Our method provides a unique new tool to improve aspects of weather and climate models important for simulating phenomena such as heat waves. Key Points: The relative warming rate diagnostic is used to assess soil drying impacts on surface heat fluxes in climate models This diagnostic is shown to be a very good indicator of modeled evaporative fraction evolution during dry downs Models capture dry spell evapotranspiration dynamics well in arid zones but struggle in continental climate zones